Convexity of Certain Integral Operators Defined by Struve Functions - Shahid Mahmood; Sana Mahroz; Ayesha Rafiq; Sarfraz Nawaz Malik; Mohsan Raza (Journal of Function Spaces)
This article deals with some functional inequalities involving Struve function, generalized Struve function, and modified Struve functions. We aim to find the convexity of the integral operator defined by Struve function, generalized Struve function, and modified Struve functions.